The genus Teijsmanniodendron Koord. (Lamiaceae) - De Kok, R.P.J.; Go, Rusea; A., Latiff (Springer Verlag, 2009)
A revision of the genus Teijsmanniodendron Koord.(Lamiaceae) is presented with a summary of its taxonomic history, keys, full descriptions, distribution maps, conservation assessments, ecological information and ethno-botanical notes. In this treatment, 23 species are recognised, one new combination is made: Teijsmanniodendron havilandii (Ridl.) G. Rusea, 14 names are placed into synonymy for the first time, one species is neotypified, five are lectotypified and six new species are described: T. bullatum G. Rusea, T. latiffii G. Rusea, T. obscurinerve G.Rusea, T. punctatum G. Rusea, T. renageorgeae G. Rusea and T. zainudinii G. Rusea. One species name is validated, T.scaberrimum Kosterm. ex G. Rusea and one species is excluded from the genus: T. petelotii Moldenke.